The rise of supermarkets in Zimbabwe against a tide of macroeconomic uncertainty - Maumbe, Blessing Mukabeta; Chikoko, Laurine (Routledge, 2021)
Zimbabwe has experienced a rise in supermarkets despite its volatile macroeconomic environment. Using data elucidated from key informants in the supermarket retail sector, the study observes that Zimbabwe is still relatively attractive to foreign investors as its food retail sector is not yet saturated. Zimbabwe’s supermarket expansion is driven by the entry of global, regional, and home-grown chains, growing urbanisation and an upsurge in consumerism. Unlike other African countries, Zimbabwe supermarket sector is unique due to its historical footprint, macroeconomic and policy uncertainty. Supermarket development challenges include exclusion of small farmers, modernising procurement systems, difficult operating environment characterised by liquidity crisis, hyperinflation, energy shortages, and deficient infrastructure. Future supermarket growth could emerge from a more stable macroeconomic environment, improved backbone infrastructure, upgrading value chains and penetration of untapped markets in second tier cities and small rural towns.